Outbreaks of Mycobacterium tuberculosis MDR strains differentially induce neutrophil respiratory burst involving lipid rafts, p38 MAPK and Syk - Romero, María Mercedes (2014)
Background Neutrophils (PMN) are the first cells to infiltrate the lung after infection, and they play a significant protective role in the elimination of pathogen, by releasing preformed oxidants and proteolytic enzymes from granules and generating ROS, thus limiting inflammation by succumbing to apoptosis. In a previous study, we found marked differences in ROS-induced apoptosis between two Mycobacterium tuberculosis (Mtb) strains, M and Ra, representative of widespread Mtb families in South America, i.e. Haarlem and Latin-American Mediterranean (LAM), being strain M able to generate further drug resistance and to disseminate aggressively. Methods In this study we evaluate the nature of bacteria-PMN interaction by assessing ROS production, apoptosis, lipid raft coalescence, and phagocytosis induced by Mtb strains. Results Dectin-1 and TLR2 participate in Mtb-induced ROS generation and apoptosis in PMN involving p38 MAPK and Syk activation with the participation of a TLR2-dependent coalescence of lipid rafts. Further, ROS production occurs during the phagocytosis of non-opsonized bacteria and involves α-glucans on the capsule. In contrast, strain M lacks the ability to induce ROS because of: 1) a reduced phagocytosis and 2) a failure in coalescence of lipid raft. Conclusions The differences in wall composition could explain the success of some strains which stay unnoticed by the host through inhibition of apoptosis and ROS but making possible its replication inside PMN as a potential evasion mechanism. Innate immune responses elicited by Mtb strain-to-strain variations need to be considered in TB vaccine development